A Critical Appraisal of General Science Content of Class VII Textbooks - Singh, Swati (INDIAN EDUCATIONAL REVIEW, 2011)
General Science is being taught as an integral part of general education, as it equips the learner with the basic awareness of his physical and biological environment. In this Endeavour, the ‘Content’ aspect of General Science plays a crucial role as it provides a theme or keynote for the instructional process. Thus the effectiveness of any instructional process is largely determined by the content and it presentation. Content of General Science with special emphasis on the term ‘General’ is a finest essence of those scientific facts, concepts and principles that are of general importance to a learner, providing general awareness of his environment. In order to remain realistic it needs to accommodate the ongoing changes in the environment to let the learner be conscious of recent evolution occurring as a result of scientific and technological progress. It is its auto accelerating nature and the fact that nothing is absolute in science that makes an urgent and recurring demand for periodical updating of its content. Thus to remain relevant and meaningful, content needs to be critically evaluated, updated and restructured on the regular basis. Textbooks being an effective tool to present the content, researcher felt the need to critically appraise the General Science content of Class VII textbooks prescribed by Rajasthan Board of Education in terms of its relevance and adequacy. Content was found to be environment oriented making an attempt to develop a basic awareness and understanding of the environment in the learner.